Maternal Prepregnancy Obesity is an Independent Risk Factor for Frequent Wheezing in Infants by Age 14 Months. Issue 1 (5th December 2012) - Guerra, Stefano; Sartini, Claudio; Mendez, Michelle; Morales, Eva; Guxens, Mònica; Basterrechea, Mikel; Arranz, Leonor; Sunyer, Jordi
Abstract Background: Maternal prepregnancy obesity has been linked to the offspring's risk for subsequent asthma. We determined whether maternal obesity is associated with increased risk of wheezing phenotypes early in life. Methods: We used data on 1107 mother–child pairs from two birth cohorts from the INMA–INfancia y Medio Ambiente project. Maternal height was measured and prepregnancy weight self‐reported at enrolment (on average at 13.7 ± 2 weeks of gestation). Maternal prepregnancy body mass index was categorised as underweight, normal, overweight and obese according to WHO recommendations. Information on child's wheezing was obtained through questionnaires up to the age of 14 (±1) months. Wheezing was classified as infrequent (<4 reported wheezing episodes) or frequent (≥4 episodes). Weight and length of infants were measured by trained study staff at 14.6 (±1) months of age and weight‐for‐length z‐scores computed. Results: Although maternal obesity did not increase the risk of the child to have any or infrequent wheezing, children of obese mothers were more likely to have frequent wheezing than children of normal‐weight mothers (11.8% vs. 3.8%; P = 0.002). In fully adjusted multinomial logistic regression models, including infants' weight‐for‐length z‐scores and other covariates, maternal prepregnancy obesity was associated with increased risk of frequent [adjusted relative risk (RR) 4.18, 95% confidence interval (CI) 1.55, 11.3] but not infrequent (RR 1.05 [95% CI 0.55, 2.01]) wheezing in their children. Conclusions: Maternal prepregnancy obesity is independently associated with an increased risk of frequent wheezing in the infant by the age of 14 months. These findings add evidence on the potential effects of in utero exposures on asthma‐related phenotypes.